基于VERICUT非圆齿轮磨齿虚拟加工研究 - 李建刚; 俞春华; 王琳; 谷鹏; 李泽湘 (Jixie chuandong)
The virtual noncircular gear grinding NC machine tool is set up in VERICUT.Based on the principle of noncircular gear grinding by forming grinder,the movement data is calculated and G-code is compiled.The machine tool model is built up in VERICUT,the qualified controller is choosed and the corresponding parameters is set.The simulation of noncircular gear grinding is carried out in VERICUT,and detailed analysis and discussion of the interference of virtual machining is given,and solutions is provied to these problems.Through this virtual machine tool,the correctness of the theory of noncircular gear grinding is verified and a reliable basis is provied for the actual machining.